2017
DOI: 10.1037/bul0000095
|View full text |Cite
|
Sign up to set email alerts
|

Who’s biased? A meta-analysis of buyer–seller differences in the pricing of lotteries.

Abstract: A large body of empirical research has examined the impact of trading perspective on pricing of consumer products, with the typical finding being that selling prices exceed buying prices (i.e., the endowment effect). Using a meta-analytic approach, we examine to what extent the endowment effect also emerges in the pricing of monetary lotteries. As monetary lotteries have a clearly defined normative value, we also assess whether one trading perspective is more biased than the other. We consider several indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 145 publications
(203 reference statements)
4
26
1
Order By: Relevance
“…Another explanation of the endowment effect, which similarly does not require loss aversion, comes from Weaver and Frederick () and Isoni () (see also Simonson & Drolet, ; Yechiam, Ashby, & Pachur, ). These authors provide a differential reference price account.…”
Section: Part 2: Evidence For Loss Aversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation of the endowment effect, which similarly does not require loss aversion, comes from Weaver and Frederick () and Isoni () (see also Simonson & Drolet, ; Yechiam, Ashby, & Pachur, ). These authors provide a differential reference price account.…”
Section: Part 2: Evidence For Loss Aversionmentioning
confidence: 99%
“…In addition, the status quo bias occurs even when the status quo and change options are otherwise equivalent and thus not coded in terms of losses and gains (Gal, 2006; replicated in this article) Endowment effect Kahneman et al (1990) Participants indicate a higher WTA than WTP for the same good Loss and gain are confounded with inaction and action as well as other factors. When losses and gains are decoupled from inaction and action in the retention paradigm, no evidence for loss aversion is present (Gal & Rucker, 2017a; see also Isoni, 2011;Yechiam et al, 2017;Weaver & Frederick, 2012) Risky bet premium Tversky & Kahneman (1992) Participants demand a substantial premium over an expected value of zero to accept a bet with even odds of gain and loss. It is thought that the possible loss of money looms larger than the possible gain of money Inaction and action are confounded with loss and gain; when losses and gains are decoupled from inaction and action, no evidence for loss aversion is present (Ert & Erev, 2013;Gal, 2006;Yechiam & Hochman, 2013) Hedonic impact ratings…”
Section: Riskless Choicementioning
confidence: 99%
“…The task was presented in the form of a game show called “Keep or sell?” (“Behalten oder Verkaufen?”). We used selling rather than buying prices because the former have been shown to deviate less from gambles' EVs than the latter (however, both paradigms elicit responses strongly linked to EVs; see Yechiam et al, ); in general, both formats are suitable for exposing participants to different risk–reward structures. To motivate participants to indicate their true valuations of the gambles, we implemented a Becker‐DeGroot‐Marschak auction (Becker et al, ) as follows: Participants entered a price at which they would be willing to sell each gamble by moving the mouse along a rating scale (0 E $ − 2,500 E $) and confirming the value with a click.…”
Section: Methodsmentioning
confidence: 99%
“…In pseudocode, We excluded trials in which participants indicated prices that exceeded the payoff offered in the gamble by more than 100E$, as this suggests lack of attention to the task (we did the same in Experiment 2). We used this rather liberal exclusion criterion for two reasons: First, as a recent meta-analysis shows, selling prices frequently exceed gambles' EVs ( Yechiam et al, 2017, Table 2). Second, the EV of a gamble becomes harder to compute given four-digit payoffs (0 − 2, 500E$), compared with smaller payoff ranges.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…("Behalten oder Verkaufen?"). We used selling rather than buying prices because the former have been shown to deviate less from gambles' EVs than the latter (however, both paradigms elicit responses strongly linked to EVs; see Yechiam et al, 2017); in general, both formats are suitable for exposing participants to different risk-reward structures. Experiments were coded in PsychoPy (Peirce, 2007).…”
Section: Overview Of Experiments and Hypothesesmentioning
confidence: 99%